2019
DOI: 10.1016/j.cmet.2019.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Oncogene Amplification in Growth Factor Signaling Pathways Renders Cancers Dependent on Membrane Lipid Remodeling

Abstract: Advances in DNA sequencing technologies have reshaped our understanding of the molecular basis of cancer, providing a precise genomic view of tumors. Complementary biochemical and biophysical perspectives of cancer point toward profound shifts in nutrient uptake and utilization that propel tumor growth and major changes in the structure of the plasma membrane of tumor cells. The molecular mechanisms that bridge these fundamental aspects of tumor biology remain poorly understood. Here, we show that the lysophos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
132
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(151 citation statements)
references
References 61 publications
7
132
0
Order By: Relevance
“…As mentioned above, also increased levels of saturated fatty acyl chains in membrane lipids have been coupled to the presence of more lipid rafts. In a recent study of the effects of lysophosphatidylcholine acyltransferase 1 (LPCAT1) in glioblastoma cells, the increase of disaturated PC species, especially PC 32:0, was taken as evidence for the importance of such lipids and lipid rafts for oncogenic signaling [116]. A commentary article concluded that these data in fact were "tying lipid rafts to oncogenic signaling" [117].…”
Section: More Lipid Rafts In Cancer?mentioning
confidence: 99%
“…As mentioned above, also increased levels of saturated fatty acyl chains in membrane lipids have been coupled to the presence of more lipid rafts. In a recent study of the effects of lysophosphatidylcholine acyltransferase 1 (LPCAT1) in glioblastoma cells, the increase of disaturated PC species, especially PC 32:0, was taken as evidence for the importance of such lipids and lipid rafts for oncogenic signaling [116]. A commentary article concluded that these data in fact were "tying lipid rafts to oncogenic signaling" [117].…”
Section: More Lipid Rafts In Cancer?mentioning
confidence: 99%
“…There are clear understanding on the heightened choline metabolism in cancer cells and tissues that support the progression, invasion and metastasis of cancer cells (9)(10)(11)(12)(13)(14)(15)(16)(17). In other way, cancer cells are known to divert the dietary source including choline to support the metabolic needs of breast carcinoma and other cancer cell types (11)(12)(13)(14)(15)(16).…”
Section: Level Of Choline and Phosphorylcholine In Nailsmentioning
confidence: 99%
“…Therefore, comprehensive and novel approaches are warranted to meet the requirements of early diagnosis, monitoring of drug response and new modalities of treatment options (3)(4)(5)(6). Therefore, new area of genomics, proteomics, transcriptomics, epigenomic and metabolomics is set to make advancement in exploring novel classes of biomarkers that can assist in the early detection and drug response monitoring avenues in a global context and Indian setting (3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations